Electronic structure of phosphorus and arsenic d-doped germanium - Carter, Damien; Warschkow, O.; Gale, Julian; Scappucci, G.; Klesse, W.; Capellini, G.; Rohl, Andrew; Simmons, M.; McKenzie, D.; Marks, Nigel (American Physical Society, 2013)
Density functional theory in the LDA+U approximation is used to calculate the electronic structure ofgermanium d doped with phosphorus and arsenic. We characterize the principal band minima of the twodimensional electron gas created by d doping and their dependence on the dopant concentration. Populated first at low concentrations is a set of band minima at the perpendicular projection of the bulk conduction band minima at L into the (kx ,ky ) plane. At higher concentrations, band minima at and become involved. Valley splittings and effective masses are computed using an explicit-atom approach, taking into account the effects of disorder in the arrangement of dopant atoms in the d plane.